2006
DOI: 10.1158/1078-0432.ccr-06-2019
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Anthrax Lethal Toxin Therapy Produces Regressions of Subcutaneous Human Melanoma Tumors in Athymic Nude Mice

Abstract: Purpose: Anthrax Lethal Toxin (LeTx), composed of protective antigen and lethal factor, catalytically cleaves mitogen-activated protein kinase (MAPK) kinases and inhibits the MAPK signaling pathways. The majority of metastatic melanomas possess the V599E BRAF mutation, which constitutively activates MAPK1/2 signaling. LeTx is cytotoxic to BRAF mutant melanoma cell lines in vitro, whereas most normal cells are resistant to this toxin. In this study, we determine the in vivo potency and safety of systemically ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…The in vivo dose was based on the result of previous studies that have shown using 10 Ag protective antigen plus 2 Ag lethal factor per mouse, effective but not lethal, as the standard dose for in vivo experiment (27,28). Another study done by Abi-Habib et al also showed that 5:1 ratio of protective antigen to lethal factor produced significant tumor growth inhibition on melanoma (30). An increased necrotic area was observed in LeTx-treated sections compared with vehicle controls after H&E staining (note the decreased viable rim in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo dose was based on the result of previous studies that have shown using 10 Ag protective antigen plus 2 Ag lethal factor per mouse, effective but not lethal, as the standard dose for in vivo experiment (27,28). Another study done by Abi-Habib et al also showed that 5:1 ratio of protective antigen to lethal factor produced significant tumor growth inhibition on melanoma (30). An increased necrotic area was observed in LeTx-treated sections compared with vehicle controls after H&E staining (note the decreased viable rim in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of MAPK signaling with either LeTx or a small-molecule MKK inhibitor triggers apoptosis in human melanoma cells (28,29). LeTx also causes tumor regression in human melanoma xenograft models (28,30).…”
Section: Introductionmentioning
confidence: 99%
“…We reported recently that LT, which can inactivate MEK1/2 and other MEKs by enzymatic cleavage, is selectively toxic to human melanoma cell lines having the BRAF mutation but not to those with the RAS mutations (14). This LT selective toxicity to human melanomas with BRAF V600E was verified in an experimental therapy of SK-MEL-28 melanoma xenografts in athymic mice (15). However, the fact that anthrax LT is an important virulence factor in anthrax pathogenesis and has recognized toxicity to mice (16) means that wild-type LT might not be accepted for use in human patients.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, it was shown that human melanoma cell lines with the BRAF mutation are sensitive to LT, whereas those without the mutation are generally resistant (14). The anti-melanoma efficacy of LT was further recapitulated in vivo (15). However, LT, a major virulence factor of B. anthracis, has recognized in vivo toxicity and thus might not be safe to use in human cancer patients (16).…”
mentioning
confidence: 99%
“…The amount of LeTx required for a half-maximal effect on growth (GI 50 ) was 1.3 F 0.2 ng/mL. By comparison, the GI 50 for melanoma cells is 0.03 ng/mL (20). Similarly, U0126 inhibited cell proliferation after 48 to 72 h of treatment ( Supplementary Fig.…”
Section: Mkk Signaling Is Required For Cell Proliferation In Vitromentioning
confidence: 95%